Perlindungan Konsumen Jasa Parkir Pusat Perbelanjaan - Yatini, Yatini; Ayu Ratna Sari, Mieke Yustia; Zazili, Ahmad (PROGRESIF: Jurnal Hukum, 2023)
The implementation of parking at Samarinda City Mall is carried out using the parking model and parking space leases, with variations in standard clauses. Potential disputes between the parties in this legal relationship can occur due to damage or loss caused by the actions of third parties, which have an impact on consumer losses. Variations in the implementation of parking have an impact on legal uncertainty which results in non-optimal legal protection for consumers of parking services. The research method used is empirical juridical supported by factual data obtained from research at the Samarinda City Mall. The results of the study show that the management and arrangement of parking at the Samarinda Mall is constructed as a parking agreement, the manager is responsible for damage and loss of vehicles using parking services. The standard clause on parking tickets is an exoneration clause, while the standard clause on parking space leases is not an exoneration clause. Even though BPSK Kota Samarinda has supervisory authority for standard clauses, its implementation is less effective. Supervision can be carried out by the permit giver for effective guidance and administrative sanctions. The implementation of parking space leases at the Samarinda Mall must be disciplined, because it is an avoidance of the responsibility of business actors, as an effort to optimize consumer protection.